Underground Cable Fault Detection System - A. S. Pawar; S. N. Sondkar; S. G. More; V. B. Tarate (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This work Underground Cable Fault Detector is used for identifying faults in the underground cable. Underground cables are prone to a wide variety of faults due to underground conditions, wear and tear, rodents etc. Diagnosing fault source is difficult and entire cable should be taken out from the ground to check and fix faults. The project work is intended to detect the location of fault in underground cable lines from the base station in km using a Arduino microcontroller. To locate a fault in the cable, the cable must be tested for faults. This prototype uses the concept of Ohms law. The current would vary depending upon the length of fault of the cable. In the urban areas, the electrical cable run in underground instead of overhead lines. Whenever the fault occurs in underground cable it is difficult to detect the exact location of the fault. The prototype is modelled with a set of wires representing cable length in km and fault creation is made by a set of switches at every known distance to cross check the accuracy of the same. In case of fault, the voltage across series wires changes accordingly, which is then fed to an ADC to develop precise digital data to a programmed Arduino that further displays fault location in distance. The fault occurring distance is displayed on a 16X2 LCD interfaced with the microcontroller.
Keywords: Arduino Uno; Step Down Transformer; LCD